Biomechanical analysis of running: correlation between main frontal findings and foot and ankle injuries in amateur runners - Bittar, Cintia Kelly; Alves-Jr., Wilson Mello; Rodrigues, Vitor Mendes; Yamashita , Emilly Sayuri; Ribeiro, Felippe; Vasconcelos, Rodrigo Antunes de (Brazilian Journal of Case Reports, 2023)
To correlate the most prevalent ankle and foot injuries in amateur runners with the biomechanical analysis of running, considering the patterns of frontal analysis evaluated in a private orthopedic and physical therapy service. Retrospective analysis of 56 medical records of amateur runners with ankle and foot complaints who underwent biomechanical assessment of running in an Orthopedics and Physical Therapy clinic in 2017 and 2018. Lesions found: Shin splints (26.78%); plantar fasciitis (21.42%); Achilles tendinopathy (21.42%); Tibial Stress Syndrome (8.92%); lower limb stress fractures (5.35%); posterior tibial tendonitis (5.35%); peroneal tendinopathy and ankle sprain (7.14%); talar chondral lesion (1.78%) and Morton’s neuroma (1.78%). The biomechanical analysis showed that the most common findings were valgus knees, with 43 cases (76.78%), followed by pelvic drop and center of mass vertical oscillation, with 40 cases each (71.42%) and hamstring retraction, with 37 cases (66.07%). Among the least prevalent, varus knees and supinated foot stand out, with two cases each (3.57%) and medial or lateral heel whip (5.35%, 3 cases). The most prevalent findings were valgus knee, pelvic drop, center of mass vertical oscillation, and hamstring retraction. Among the least present, stand out the varus knees, the supinated foot and the medial or lateral heel whip.